2021
DOI: 10.3390/biomedicines9060599
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A1/Toll-Like Receptor-4 Axis, an Important Link between Inflammation and Outcome of TBI Patients

Abstract: Traumatic brain injury (TBI) is one of the leading causes of mortality and disability worldwide without any validated biomarker or set of biomarkers to help the diagnosis and evaluation of the evolution/prognosis of TBI patients. To achieve this aim, a deeper knowledge of the biochemical and pathophysiological processes triggered after the trauma is essential. Here, we identified the serum amyloid A1 protein-Toll-like receptor 4 (SAA1-TLR4) axis as an important link between inflammation and the outcome of TBI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Besides Itih4, ferritin light polypeptide 1 (Ftl1) and serum amyloid a1 (Saa1) were upregulated by AS + TBI in relation to sham mice (Figure 5E,F). Of note, higher Saa1 levels were previously reported in TBI patients 52 . Apolipoprotein N (Apon) was downregulated approximately sixfold after AS + TBI (Figure 5E,F).…”
Section: Resultssupporting
confidence: 57%
“…Besides Itih4, ferritin light polypeptide 1 (Ftl1) and serum amyloid a1 (Saa1) were upregulated by AS + TBI in relation to sham mice (Figure 5E,F). Of note, higher Saa1 levels were previously reported in TBI patients 52 . Apolipoprotein N (Apon) was downregulated approximately sixfold after AS + TBI (Figure 5E,F).…”
Section: Resultssupporting
confidence: 57%
“…The role of SAA1 in Numerous studies have shown that SAA1 regulates the biological functions of various cells principally by binding with its potential receptors or other effector molecules [13]. In particular, potential receptors of SAA1 have been identified in immune cells, including P2RX7, CD36, recombinant Scavenger Receptor Class B Member 1 (SCARB1), valosincontaining protein (VCP), and TLR2/4 [14,23,[49][50][51][52]. For example, SAA1 activates the nucleotide-binding domain leucine-rich repeat (NLR) family pyrin domain containing 3 (NLRP3) inflammasome via P2RX7, leading to inflammatory activation and IL-1β secretion of macrophages [53].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that SAA1 is an agonist of TLR4 [14], and SAA1 increased neuroinflammation through activating TLR4-related signaling in glial cells in a recent study [23]. In addition, TLR4 is a specialized receptor protein found in immune cells [24,25] and is distributed on the surface of platelets, monocytes, and endothelial cells, and the activation of TLR4 signaling is also an important factor accelerating platelet aggregation, monocyte inflammatory phenotypic differentiation, and endothelial cell activation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…After burn injury, a significant amount of necrotic and apoptotic debris is released that may warrant this induction of CRP in EVs. SAA1 also promotes phagocytosis in macrophages and is a ligand for TLR4 [ 48 , 49 , 50 ], which is induced early after burn injury [ 7 , 20 ]. Both SAA1 and CRP correlated with %TBSA burn injury across all subjects and length of hospital stay in females.…”
Section: Discussionmentioning
confidence: 99%